Academic staffing patterns in nursing colleges in Natal and Transvaal - E. T. Khumalo; L. R. Uys (AOSIS, 1993)
The purpose of this study was to determine post structure in Natal and Transvaal nursing colleges, the extent to which these posts are filled by suitably qualified tutors and the workload of the academic staff in relation to post level and qualifications. Two hundred and thirty-three nurse tutors participated in the study. Data were collected by a questionnaire developed by the researcher. Findings revealed that the post structure was similar in Natal and Transvaal nursing colleges and the workload of nurse tutors was recorded.